Processing line for industrial radiation-thermal synthesis of doped lithium ferrite powders; IOP Conference Series: Materials Science and Engineering; Vol. 110 : Radiation-Thermal Effects and Processes in Inorganic Materials (RTEP2015) - Surzhikov A. P. Anatoly Petrovich; Galtseva (Gal’tseva) O. V. Olga Valerievna; Vasendina E. A. Elena Aleksandrovna; Vlasov V. A. Vitaliy Anatolievich; Nikolaev E. V. Evgeny Vladimirovich (2016, 2016)
Title screen